Social relationships and social support among post‐war youth in Northern Uganda. (7th October 2015) - De Nutte, Leen; Okello, James; Derluyn, Ilse
Abstract : Although social relationships and social support are salient factors for post‐war adolescents' psychosocial coping and adjustment, there is only limited information regarding war‐affected adolescents' views on social support and the relationships within which social support is provided. This study therefore explored both elements among a clinical sample of 20 adolescents living in post‐war Northern Uganda. Following Braun and Clarke's thematic analysis, we found a prominent role of the biological mother and other primary biological family members in the upbringing of our participants. Spiritual and material support were perceived to be the most important type of support, respectively, while the adolescents were growing up and in their current lives. These findings provide support for the perception that caregiving systems are adaptable to particular sociocultural contexts. Further, the importance of particular functions of social support could signify a potentially selective buffering effect of these functions in adverse contexts. Because of the importance of the primary biological family and the salient role of parent–child relationships in the face of adversity, future research needs to focus on this particular kind of social relationship in contexts of prolonged collective violence.